Preterm human milk composition and dietary intake of breastfeeding mothers in the Indonesian population - Putri Maharani Tristanita Marsubrin; Rinawati Rohsiswatmo; Damayanti R. Sjarif (Indonesian Pediatric Society, 2021)
Background Human milk consumption is a protective factor against infection. However, the high variability of human milk composition makes it difficult for clinicians and researchers to assess the adequacy of nutritional intake. Objective To identify the nutritional profiles and composition of premature human milk and dietary intake of breastfeeding mother. Methods Human milk specimens were collected from mothers who gave birth to very premature and/or very low birth weight infants. Infants had been admitted to the Neonatology Unit of Dr. Cipto Mangunkusumo Hospital, Jakarta. The milk specimens were analyzed with a mid-infrared milk analyzerTM (MIRIS) for four weeks, and maternal dietary macronutrient intake was determined with food record questionnaires on food consumption frequency and food recall. Results Significant changes in nutritional composition of human milk were observed, with the fat concentration and calories increasing with time, and protein concentration decreasing with time. There were no significant differences observed in carbohydrate concentration of milk over the four weeks (P=0.447). Maternal intake of protein, carbohydrates, fat and calories was lower than the recommended values for breastfeeding women. Conclusion The macronutrient (protein and fat) and energy contents of human milk change weekly. Dietary intake of breastfeeding women are lower than recommended values.